Analisis Faktor Penentu Kompetensi Berdasarkan Konsep Knowledge, Skill, Dan Ability (KSA) Di Sentra Kaos Suci Bandung - Iwan Sidharta; Dina Lusyana (STMIK Mardira Indonesia, Bandung, 2014)
Competency-Based Analysis Concept Determinants of Knowledge, Skill, and Ability (KSA) In Center of Clothing Suci, Bandung. It is inevitable that the competence is one of the determining factors in the success of businesses, especially SMEs. By having sufficient competence will result in optimal performance for SMEs. SMEs in Sentra Kaos Suci Bandung is one of the leading sectors of the local government of Bandung which is expected to provide economic impact for the community and the government. The purpose of this study was to determine the influence of factors that affect the competence is based on the concept of knowledge, skills and abilities in Sentra Kaos Suci Bandung. Exploratory research methods of data analysis techniques using Structural Equation Modelling (SEM), component-based Partial Least Squares (PLS). The number of respondents as many as 54 SMEs with the data collection technique with purposive sampling. Results of the study indicate where the most influential factor is the major factor of capacity (ability) while the factors that have an influence tekecil is a factor of knowledge (knowledge) on the competence of SMEs in Sentra Kaos Suci Bandung. Keywords: knowledge; skills; ability; competence; SMEs